2017
DOI: 10.15446/dyna.v84n203.62742
|View full text |Cite
|
Sign up to set email alerts
|

Manufacturing and evaluation of Chitosan, PVA and Aloe Vera hydrogels for skin applications

Abstract: The aim of this research was to develop membranes of polyvinyl alcohol (PVA) and chitosan (CH), capable of absorbing an Aloe Vera solution and gradually releasing to accelerate wound healing. The methodology involved varying the membrane's composition using Chitosan and Polyvinyl Alcohol at 5 and 10% w/v, and implementing different PVA/CH relations of 30/70, 50/50 and 70/30 (v/v) and embed them in a 2% (v/v) Aloe Vera solution to create hydrogels. Once hydrogels were obtained, they were characterized by Infrar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 14 publications
1
18
0
1
Order By: Relevance
“…Polyvinyl alcohol (PVA) hydrogels [ 15 , 16 , 17 ], dicarboxylic acids (DCAs) [ 18 ] and cyclodextrins (CDs) [ 19 , 20 ] are commonly used as biomaterials because they have a high biocompatibility and are FDA-approve. CDs were selected because they are able to form inclusion complexes (host-guest type) with several classes of compounds including hydrophobic drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Polyvinyl alcohol (PVA) hydrogels [ 15 , 16 , 17 ], dicarboxylic acids (DCAs) [ 18 ] and cyclodextrins (CDs) [ 19 , 20 ] are commonly used as biomaterials because they have a high biocompatibility and are FDA-approve. CDs were selected because they are able to form inclusion complexes (host-guest type) with several classes of compounds including hydrophobic drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 2b shows the spectrum of Ch-PVA-NaOH-TPP before the adsorption process. It shows the signal 3354 cm −1 of the chitosan OH group, with a slight increase to 3359 cm −1 and the band at 3323 cm −1 of the OH group of the PVA loses definition [57]. A slight decrease of 2918 cm −1 is observed in the 2920 cm −1 signal of the CH group of the chitosan.…”
Section: Characterization By Fourier Transform Infrared Spectroscopymentioning
confidence: 93%
“…20 Nonetheless, due to the lack of bioactivity in PVA, it is usually used in combination with other biomaterials or biomolecules to promote its ultimate biological effectiveness. 18,21,22 Previous studies indicated the significant wound healing potential of egg white (EW) as a natural biomaterial that can form a gel network of proteins. 23−26 EW usage is recommended due to its high bioactivity, availability, ease of use, and low production costs.…”
Section: Introductionmentioning
confidence: 99%